Islamic Law Studies on the Use of Infak Fund for Land Waqf - Adwi, Farly; Syibly, Roem (Universitas Islam Indonesia, 2019)
A mosque is a device of worship and a means of gathering the first community founded by the Prophet. At the time of the Prophet Muhammad the mosque had become the center of activity and information. In this activity, it certainly requires funds to run well. One of the sources of the mosque's funding is Infak. Infak is related to the alms of sunnah given for religious activities or for the public interest. One of the mosques that uses Infak funds to purchase land that will later be used as waqf land, namely Adz-Dhikra Mosque. The research intends to conduct research on mosque infak for the purchase of land which will later be used as waqf land, and one of the mosques that uses Infak funds to purchase land is Adz-Dhikra mosque whose formulation is how the contract, the waqif, and the endowments The type of research used is field research and literature study. This research is located at Adz-Dzikra Mosque, Jirak Hamlet, Bokoharjo Village, Prambanan Sub-District, Sleman Regency. Data collection technique was by interview and literature study. The results of this study indicate that in purchasing waqf land at the Adz-Dhikra Mosque is using Infak fund, which is collected from the surrounding community. In the Islamic Islamic law, it is illegal, but it is legally administered by the Law.Key words: Infak, Waqf.